Soicial Factors and Citizens’ Perception of the Police - Pullin, Mark (Advances in Social Sciences Research Journal, 2022)
Research examining citizen perception of the police have typically looked at expanded views of how the police interact in the community. By narrowing the focus to encompass two principles that associate citizen satisfaction with and perceptions of the police, this paper will include areas that influence satisfaction directly from citizens toward police officers themselves. Moreover, recent research stresses the importance of police/citizen relationships for positive outcomes to occur after interaction. Research regarding race and ethnicity of the citizen is reviewed as well as youth and age to provide context for this article. Demographic variables have been shown to have an impact of citizen perception of the police thus affecting how they view the police and government agencies. Police literature is reviewed as to how these demographics contribute to neighborhood level changes in attitudes toward police officers. Community policing literature and the effects it has on neighborhood social cohesion and collective efficacy is also included. This will lead into a discussion of neighborhood social cohesion and collective efficacy and their impact on citizen perceptions of the police.